From Snake Pits to Ballrooms: class, race and early rock'n'roll in Perth. Issue 2 (4th March 2017) - Trainer, Adam
Abstract: In the late 1950s, rock'n'roll as both a musical genre and a pervasive youth cultural form spread from the U.S. to emerge in various regionalized forms throughout most Western societies. Through the development of various social, technological and industrial circumstances, rock'n'roll was the first youth subculture in Perth, Western Australia to develop widespread acknowledgement across popular cultural consciousness. From its roots in working-class culture to its eventual commercial embrace by middle-class audiences, rock'n'roll developed in Perth through a set of specific circumstances linked to both racial and class-based factors, distinctive to the city as a small, isolated and predominantly suburban location. Whilst the majority of historical analysis on early rock'n'roll focuses on Australia's east coast, this paper attempts to counter that by drawing from interviews conducted with a number of individuals who were instrumental in the emergence of rock'n'roll in Perth. As such this essay delivers a social history of the style as it developed in that city, placing it at the beginning of a fundamental shift in popular music as a cultural phenomenon, and underlining the importance that a number of specific social and cultural factors including class and race played in the development of a locally specific rock'n'roll culture.